Julius Caesar, Thinking About Battle and Foreign Relations - Lendon, J. E. (Histos, 2015)
There is a symbiosis between the ways Julius Caesar thought about international relations and his mental armamentarium for thinking about battle, especially in terms of physical pressure (impetus, vis, premere, sustinere), morale (animus), and courage (virtus), with its frequent corollary, revenge. Sometimes his modes of thinking about foreign affairs drew upon battle, and sometimes the two realms of thinking drew mutually upon each other. This sharing of concepts helps us to understand the method of Caesar's Bellum Gallicum, the lack of interest Latin authors so often display in the origins of wars, and also real-world Roman aggression and its purposes, direction, and methods, as practised by Caesar and his successors.